Determination of leadership styles of boxing trainers - Turgut Kaplan; Kayhan Serın (Selcuk University, 2017)
This study aimed to determine the leadership styles of boxing trainers. For this purpose, a total of 100 male trainers who worked actively in Turkey volunteered to participate in the study. The data of the study were collected by using the leadership questionnaire which was adapted by Tiryaki (2001) from the Leadership Scale for Sports (LSS) developed by Chelladurai and Saleh (1980). The descriptive statistical analysis of the obtained data was carried out using the Kruskal Wallis and Mann-Whitney-U tests. Whether the trainers were assigned to the national team, whether they differ in terms of age, how they were assigned, their training experience and level and their leadership styles were determined. After the tests were carried out, it was observed that there was a statistically significant difference between the variables of the trainers' age, training experience and level (P lt;0.05). Apart from the variables of age, training experience and level and the leadership style of democratic behavior, it was ascertained that there was no significant relationship between the leadership styles of the boxing trainers (P gt;0.05). According to the results of the study, the leadership styles of trainers do not differ according to whether they are/have been assigned as national team trainers. In addition, apart from democratic behavior, a significant difference was not detected in the other leadership styles in terms of demographic characteristics.